MECHANICAL PERFORMANCE OF NEGATIVE POISSON’S RATIO STRUCTURES BASED ON ROTATING CONCAVE HEXAGON (MT) - WANG Zhen; CHEN GuoPing; HUI XuLong; HE Huan (Jixie qiangdu)
In order to improve the mechanical performance of the negative Poisson’s ratio structure, based on the deformation mechanism of rotating rigid body structure and concave polygon structure, conventional concave hexagon was rotated by a certain angle to obtain the negative Poisson’s ratio（NPR） structure of rotating concave hexagon. Firstly, the theoretical formulas of structural equivalent performance, such as relative density, equivalent elastic modulus, and equivalent Poisson’s ratio, were derived, and verified by simulation calculation. The finite element software LS-Dyna was used to simulate and analyze the dynamic characteristics of rotating concave hexagon and conventional concave hexagon under different impact velocities, and the relationship between energy absorption characteristics of rotating concave hexagon NPR structure and structural parameters such as cell wall thickness, rotation angle and included angle was discussed. The results show that the nominal stress-strain curves of the structure have multi-stage platform stress characteristics. Compared with conventional structure with the same mass, the new structure has longer platform stress section and better energy absorption performance. This study provides an idea for improving impact resistance of multicellular structures.